Modeling of Temperature and Aifflow Pattern In a Refrigerator - Haque, Muhammad E.; R. A., Bakar; Gan, Leong Ming; Shakaib, M. (Asian Research Publishing Network (ARPN), 2017)
Several researchers have shown that Computerized Fluid Dynamics (CFD) can be successfully used for mathematical modeling of refrigeration systems. In this paper authors developed a CFD model for a domestic no-frost refrigerator. The conservation equations of energy mass and momentum are solved by using Finite Volume Method in an environment of three dimensional unstructured mesh. Experiments were conducted on a no-frost domestic refrigerator to compare and validate the results of the CFD model. Both the results from the CFD model and experiment are qualitatively similar even though there are certain discrepancies due to some insufficient information available for the numerical model.